2020
DOI: 10.3390/ijerph17061825
|View full text |Cite
|
Sign up to set email alerts
|

Intracervical Foley Catheter Plus Intravaginal Misoprostol vs Intravaginal Misoprostol Alone for Cervical Ripening: A Meta-Analysis

Abstract: Currently, there is no meta-analysis comparing intravaginal misoprostol plus intracervical Foley catheter versus intravaginal misoprostol alone for term pregnancy without identifying risk factors. Therefore, the purpose of this study is to conduct a systematic review and meta-analysis of randomized control trials (RCTs) comparing concurrent intravaginal misoprostol and intracervical Foley catheter versus intravaginal misoprostol alone for cervical ripening. We systematically searched Embase, Pubmed, and Cochra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 68 publications
1
12
0
Order By: Relevance
“…As a matter of fact, the use of intracervical FC plus vaginal misoprostol has been compared with vaginal misoprostol alone in a very recent meta-analysis. In this study, Lee et al showed that induction time, uterine tachysystole, and meconium staining decrease with the combination of FC and vaginal misoprostol compared to misoprostol alone with no difference regarding the C-section rate (25).…”
Section: Discussionmentioning
confidence: 60%
“…As a matter of fact, the use of intracervical FC plus vaginal misoprostol has been compared with vaginal misoprostol alone in a very recent meta-analysis. In this study, Lee et al showed that induction time, uterine tachysystole, and meconium staining decrease with the combination of FC and vaginal misoprostol compared to misoprostol alone with no difference regarding the C-section rate (25).…”
Section: Discussionmentioning
confidence: 60%
“…As a matter of fact, the use of intracervical FC plus vaginal misoprostol has been compared with vaginal misoprostol alone in a very recent meta-analysis. In this study, Lee et al showed that induction time, uterine tachysystole, and meconium staining decrease with the combination of FC and vaginal misoprostol compared to misoprostol alone with no difference regarding the C-section rate [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…A two-sided p -value of ≤0.05 was regarded as statistically significant. Comprehensive Meta-analysis Version 3.0 (Biostat Inc., Englewood, NJ, USA) was used for data synthesis [ 68 ]. A random effect model was used to calculate effect size in meta-analysis due to potential clinical heterogeneity from different surgical indications and investigated populations.…”
Section: Methodsmentioning
confidence: 99%